Effect of Using Raw and Treated Quinoa Seeds (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
The experiment aimed to study the use of different proportions of raw and treated Chenopodium quinoa seeds by soaking in the diet in order to identify the effect on the productive performance characteristics of broilers of 42 days of age. A 336 sexed broilers (Ross 308) were distributed randomly at one-day old, with an average initial weight of 39 g/chick, divided into seven treatments, 48 chicks/treatment, each treatment included three replicates, 16 chicks/replicate (8 males and 8 females).